Impact Of Micro-Finance On The Development Of Stree Shakti Group Members (Bangladesh Journal of Agricultural Research, 2011)
Micro- finance helps the rural poor to improve their living standards and fulfill their credit needs. Stree Shakti Groups (SSGs) are new innovation in the field of rural economic development, to finance the rural women and also to satisfy their credit needs. This study mainly focuses on the impact of micro-finance on the development of SSG members. The study was undertaken in Doddaballapura taluk of Bangalore rural district of Karnataka state, India and the required data were collected from 100 SSG members and 30 non-SSG members. It was found that the number of income generating activities taken up by SSG members (five) was higher compared to non-SSG members (three) and the income generated from these activities was also higher compared to non-SSG members. There was significant growth in the amount of loan borrowed, repayment and savings over time among SSG members. SSG finance substantially enhanced employment opportunities for members compared to non-members, which led to improved income and living standard of members. Since SSGs play a major role in the development of women, there is a need to encourage more number of SSGs. The study also reveals that the performance of Non Governmental Organization (NGO) promoted SSGs was much better than Government promoted SSGs. Hence, more number of NGOs must be involved in promoting SSGs covering more womenfolk. Keywords: Micro-finance; Stree Shakti group; self help group; impact; empowerment; non-governmental organization DOI: http://dx.doi.org/10.3329/bjar.v36i2.9261 BJAR 2011; 36(2): 333-350